Financial Crisis as a Trigger or Amplifier? The Role of Financial Distress in Moderating Hexagon Fraud Factors on Financial Statement Fraud - Ananda Rinaldy, Reza; Saputra, Dian (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study uses financial strain as a moderating variable to examine the relationship between Hexagon Fraud and Financial Statement Fraud. The sample comprises 32 companies in the transportation and logistics sector listed on the Indonesia Stock Exchange for the 2020–2022 period. SEM-PLS was utilized for data analysis. The findings indicate that the danger of financial statement fraud is increased by financial pressure, ineffective monitoring, changes in the director or auditor, ego, and collusion. Financial distress strengthens the effect of auditor and director changes but does not moderate the effect of Ego and Collusion. These findings emphasize the importance of internal control and financial risk management to prevent fraud.